Penambahan Bambu Bulat Pada Balok Beton Pracetak Menggunakan Software Berbasis Elemen Hingga: Analysis of Adding Bamboo Culms on Precast Concrete Using Finite Element Based Software - Kurniawan, Eka Yudha; Umniati, B. Sri; Karyadi, Karyadi (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2024)
Post-earthquake development in Indonesia is a complex challenge that requires cross-sectoral efforts and support from various parties. Indonesia is prone to earthquakes due to its location on the Pacific Ring of Fire, an active area of earthquakes and volcanic activity. The use of precast concrete has a number of important advantages in earthquake-prone areas but the connection between joints can be a weak point if not done properly. This study will discuss the connection system, connection location, and details. The research method used is numerical analysis using finite element-based software. It is concluded that the connection system used has not been able to reach the capacity of the monolith beam without connection, while the addition of bamboo does not have a significant effect on the bending capacity of the beam.